Effect of Scour and Seismicity on the Bridge’s Response - Nordila Ahmad; Muhammad Amir Syauqi Mohd Shukri; Syuriya Mohamad; Mohd Zamri Ramli (International Journal of Integrated Engineering, 2025)
Bridges are critical points in rail and road networks, and their failure due to natural hazards like tsunamis, earthquakes, ground movements, or floods can cause significant losses. Identifying weaknesses and measuring bridge strength is crucial for disaster resilience. Current methods rely heavily on engineering judgment, lacking dependable quantitative evaluations. This framework offers a comprehensive approach to creating numerical simulations and assessing bridge resilience against multiple hazards. The project involves simulating a 130-metre pre-stressed concrete bridge exposed to seismic and scour depth hazards using the CSI Bridge software. The simulations consider three scour depth levels (1Df, 1.5Df, and 2Df), five earthquakes, and varying seismic intensities (0.25 to 1.5 Peak Ground Acceleration, PGA, with 0.125 increments). The foundation depth (Df) is 2.5 metres, and simulations are run under clay soil. Nonlinear Time History Analysis (NTHA) is employed for its suitability for inelastic beam-column elements under dynamic loading. Results indicate that increasing the scour depth from 1.5Df to 2Df increased pier displacement by 21.68% in clay.